Psychospiritual and Socioreligious Approaches to Mental Health in Islam and Christianity - Putri, Nur Helmelia; Arifinsyah, Arifinsyah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
Mental health is a multidimensional aspect of human well-being, encompassing emotional, psychological, social, and spiritual components. In religiously devout societies such as Indonesia, spiritual and communal values deeply influence how mental health is perceived and addressed. This study explores psychospiritual and socioreligious approaches to mental health by comparing Islamic and Christian perspectives. Through a qualitative-descriptive method and library-based research, the study draws upon classical theological texts, scriptural sources, and contemporary literature to analyze religious coping mechanisms, core spiritual values, and their integration into mental well-being. Findings reveal that Islam emphasizes al-nafs al-muṭma’innah (the tranquil soul), achieved through tazkiyat al-nafs (self-purification), devotion, and social responsibility. Christianity, meanwhile, centers on shalom (divine peace), fostered through personal relationship with God, hope, and communal worship. Both traditions offer distinct but complementary coping strategies that connect inner resilience with faith-based practices and collective religious life. By situating mental health within theological and sociocultural frameworks, this study contributes to the development of integrative models that bridge psychological care, spiritual meaning, and community-based support—particularly in multireligious and culturally rooted contexts.